Faktor-Faktor yang Memengaruhi Audit Report Lag dengan Spesialisasi Industri Auditor sebagai Variabel Moderasi pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2022 - Kurniawati, Rebecha Dwi (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to examine the effects of company operating complexity, audit tenure, and auditor switching on audit report lag, with auditor industry specialization as a moderating variable. This research employs a quantitative associative approach using secondary data obtained from annual reports of mining companies listed on the Indonesia Stock Exchange during the 2020–2022 period. The sample was selected using purposive sampling and consisted of 41 companies, resulting in 123 firm-year observations. Data were analyzed using Structural Equation Modeling with WarpPLS version 7.0 through model feasibility testing and hypothesis testing. The results show that company operating complexity has a negative and significant effect on audit report lag. Meanwhile, audit tenure and auditor switching do not have significant effects on audit report lag. Auditor industry specialization does not moderate the effects of company operating complexity and audit tenure on audit report lag. However, auditor industry specialization moderates the effect of auditor switching on audit report lag. These findings indicate that auditor industry specialization plays a role in reducing the impact of auditor switching on audit delay, but it does not significantly strengthen or weaken the effects of operating complexity and audit tenure.